(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aims to identify the level of both psychological comfort and job performance among a sample of high school teachers for the academic year (2019-2020). The researcher has built two tools to measure psychological comfort, and one to measure job performance. The researcher applied the two scales to a random stratified sample of (100) male and female teachers. The results showed a low level of feeling with psychological comfort among secondary school teachers and a good level of sense of job performance. There is no statistically significant difference in the level of psychological comfort according to gender. There is a significant difference in psychological comfort according to the variable of the length of service in favor of those with duration 11-more). There is no statistically significant difference in the level of job performance according to the variables of sex and the length of service. There is a correlation between psychological satisfaction and job performance. The research came out with a number of recommendations and suggestions.